Pengembangan Lembar Kerja Siswa Materi Gerak Dasar Berisi Konten Berbasis Permainan Tradisional Kalimantan Utara - Sucahyo Mas’an Al Wahid (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
form of books. The purpose of this study was to determine the quality of materials and media in locomotor, non-locomotor and manipulative learning devices containing traditional game content. The research site was carried out in class II were 20 students. The research uses a research and development approach through the Dick & Carey model with 7 stages. The results of the study on indicators of introducing the traditional game of switching stars, taxes and pickles on the content feasibility achievement with an average overall score of 3, then the demonstration indicator through pictures on the presentation achievement obtained an average score of 2.25, as well as indicators of the use and attractiveness of letters on the achievement language and readability score 2. The assessment also consists of device assessment, and LKS assessment (material expert and media expert). The assessment obtained in the assessment of learning devices obtained a percentage of 88.89% which means that it meets the valid criteria. Meanwhile, the LKS assessment is based on the validation results of material and media experts, both of which get a percentage value of 90%, which means it is valid